Canvas Business Model To Create Fundraising Strategy at LAZIS Al Haromain - Hanina Ulfati Umi Najah; A’rasy Fahrullah (ITB AAS INDONESIA Surakarta, 2023)
As LAZ grows more and more, LAZ also has new challenges to be able to keep up with crowd funding institutions in fundraising activities. So it is necessary to have a strategy and program advantages that need to be owned by each LAZ. The Jariyah Islamic Boarding School Program is one of the flagship programs offered by Lazis Al Haromain to assist the development of Islamic boarding schools. This study aims to find out how the Fundraising strategy is in obtaining infaq funds and attracting current donors at the Jariyah Islamic Boarding School Program and formulating a strategy with the Business Model Canvas. This research uses descriptive qualitative method. Data collection techniques were carried out by interviews, observation and documentation. The results of the stud y show that the current strategy being developed includes pick-up donations, campaigns through social media, the Friday jariyah movement, and offering pesantren jariyah coupons. The results of the elaboration of the strategy into the 9 elements of the Business Model Canvas show that the implementation of the strategy is quite good but based on the results of the SWOT analysis there are several elements of the business model canvas that need to be improved so that the strategy runs more optimally and has an impact on obtaining funds in the Islamic boarding school's jariyah program.